The Effect Of Giving Katuk Leaves To Post Partum Mothers To Improve Breast Milk At The Novi Lintas Timur Midwifery Clinic, Panyabungan District, Mandailing Natal Regency - Dewi Srirahayu Tinendung; Ester Selfia Napitupulu (Jurnal EduHealth, 2022)
Breast milk is the first, main and best food for babies, which is natural. Breast milk contains various nutrients needed for the growth and development of babies. One effort to increase breast milk production is by improving the quality of food that has a direct effect on milk production, namely katuk leaves. The aim of this research was to determine the effect of giving katuk leaf decoction to post partum mothers to facilitate breast milk. This research is a quantitative type with a pre-experiment design whose design uses the one group pretest-posttest design. The population in this study were 35 post partum mothers of patients at the Novi Lintas Timur Midwife Clinic. The sampling technique is Exhaustic Sampling (total sampling). Data analysis used the Wilcoxon test. The results of the study showed that the flow of breast milk in post partum mothers before and after giving katuk leaves experienced significant changes. The flow of breast milk in postpartum mothers before breastfeeding was 20 people who experienced insufficient breast milk and 15 people who had sufficient breast milk. Then after giving katuk, the smoothness of breast milk increased to 18 people and there were more than 10 people, while the smoothness of breast milk was less than 7 people. The results of statistical tests using the Wilcoxon rank test show that the p-value (0.000) < α (0.05) means that Ho is rejected, so there is a significant effect of giving katuk leaves on increasing breast milk production in post partum mothers.